Teacher and student perceptions of blended learning in Chemistry curriculum implementation in public secondary schools in Obio-Akpor Local Government Area - Nduudee, Joy Nenalebari; Enebeli, Eloka (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2024)
This study looked at Chemistry Education curriculum implementation and integrated learning in public secondary schools in Obio-Akpor Local Government Area, Rivers State. This study used a descriptive survey design as its research methodology. The study formulated two hypotheses and three research questions. 18116 Chemistry students and 189 Chemistry teachers from all of the public secondary schools in the study area made up the study's population. With the use of multi-stage sampling approaches, 301 students and 90 Chemistry professors made up the sample size. Questionnaires served as the data collection tool. The instrument's 0.88 reliability coefficient served as validation. The t-test was utilised for the hypotheses, and mean and standard deviation were employed for the analysis of the research questions. Every experiment was run at the significance level of 0.05. The study's conclusions showed that both educators and pupils in the public secondary schools in the study region possess the skills needed to use the blended learning approach to Chemistry Education curricula. Subsequent research revealed that inadequate internet access, unstable electrical supply, and expensive data plans are the main obstacles impeding the successful use of blended learning in Chemistry education. Making internet facilities available was one of the recommendations provided for the successful integration of blended learning as an instructional design in the Chemistry Education programme.